SHARIA FINANCIAL LITERACY AND INCLUSION: OPPORTUNITIES AND CHALLENGES - Anez Yuniar Pradini; Akhmad Faozan (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractFinancial literacy and inclusion are indicators of a country's economic growth. If a country's level of financial literacy and inclusion is high, then the country can be said to be a developed country. This research aims to identify opportunities and challenges in efforts to increase the sharia financial literacy and inclusion index. This research uses the Systematic Literature Review (LSR) method with a descriptive approach. The results of this research show that the opportunities for financial literacy and inclusion include; Indonesia's demographic conditions which are dominated by Generation Z and millennials, the 2024 National Digital Transformation Program, high levels of education, the popularity of financial products and services, numerous and widespread sources of information (the presence of finfluencers), increased GDP per capita. Meanwhile, the challenges faced include; the increasing number and complexity of financial products and services, the threat of cyber crime, global economic conditions, the diversity of Indonesia's demographics, and the vastness of Indonesia's territory.Keyword: Financial literacy; Financial Inclussion; Opportunity; Challenge.Â